CO2 and CH4 Wettabilities of Organic-Rich Shale - Pan, B.; Li, Y.; Wang, H.; Jones, Franca; Iglauer, Stefan (American Chemical Society, 2018)
CO 2 and CH 4 wettabilities of organic-rich shale are important physicochemical parameters that significantly influence CO 2 sequestration and CH 4 production. However, there is a serious lack of understanding of these aspects because the data available are scarce. Thus, we evaluated organic-rich shale CO 2 and CH 4 wettabilities (i.e., brine/shale/gas systems) through advancing and receding brine contact angle measurements as a function of pressure, temperature, salinity, and ion type (as these can vary significantly in underground formations). The results indicated that the brine contact angles for both CO 2 /CH 4 -brine-shale systems increased with pressure and salinity, but decreased with temperature. However, these effects were much less significant for CH 4 . Furthermore, the brine contact angles for the CO 2 -brine-shale system reached 180° (i.e., the shale was completely wetted by CO 2 ) when the pressure reached 30 MPa at 343 K and ∼9 MPa at 298 K. The brine contact angles for the analogue CH 4 systems was much lower (50°-90°), only indicating weakly water-wet to intermediate-wet conditions. Finally, the brine contact angles for CO 2 -brine-shale system were also larger for divalent ions (Ca 2+ , Mg 2+ ) than for monovalent ions (Na + , K + ), while ion type had no significant influence on CH 4 wettability. However, a similar CO 2 /CH 4 density resulted in a similar wettability. Consequently CH 4 could not be used as a proxy for predicting CO 2 storage capacities, unless they have similar densities.